Ginsenoside Rg1 improves Alzheimer's disease by regulating oxidative stress, apoptosis, and neuroinflammation through Wnt/GSK‐3β/β‐catenin signaling pathway. (31st March 2022) - Yang, Yi; Wang, Limei; Zhang, Caijun; Guo, Yuqian; Li, Jintao; Wu, Chao; Jiao, Jianlin; Zheng, Hong
Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder that can cause cognitive impairment. Ginsenoside Rg1 (Rg1) has a significant neuroprotective effect on animals with memory impairment. However, the mechanism of how Rg1 mediates the Wnt signaling pathway and improves cognitive function by regulating oxidative stress, apoptosis, and neuroinflammation is still unclear. In this study, the spatial memory ability of tree shrews was tested by Morris water maze, the expression levels of amyloid protein (Aβ1‐42), ionized calcium‐binding adapter molecule 1 (iba‐1), nitrotyrosine (NT), and 8‐hydroxyguanine (8‐OHG) were detected by immunohistochemistry. Subsequently, the activity of catalase (CAT) and the glutathione peroxidase (GSH‐Px) was, respectively, measured by the ammonium molybdate method and the 5, 5′‐dithiobis (2‐nitrobenzoic acid). Furthermore, the malondialdehyde (MDA) concentration was determined by the thiobarbituric acid test. Finally, the expression levels of Beta‐secretase (BACE1), superoxide dismutase (SOD), BCL2‐Associated X (Bax), B‐cell lymphoma‐2 (Bcl‐2), caspase‐anti‐apoptotic factor Cleaved‐caspase‐3 (Caspase‐3), microtubule‐associated proteins 2 (MAP2), Neuronal nuclear antigen (NeuN), as well as the phosphorylation of GSK‐3β and β‐catenin were detected by Western blot. This study implied that Rg1 reduced the phosphorylation of Tau protein, the deposition of Aβ1‐42, and the expression of BACE1. It also showed that Rg1 increased the antioxidant activity of SOD, CAT, GPx, and instead reduced the oxidation products of NT, 8‐OHG, and MDA, as wells as the inflammatory factor interleukin‐1 and iba‐1. It further showed that Rg1 increased the ratio of Bcl‐2 to Bax and expression of neuronal markers MAP2 and NeuN, but instead reduced the expression of Caspase‐3, GSK‐3β, and β‐catenin. In conclusion, by regulating the Wnt/GSK‐3β/β‐catenin signaling pathway, Rg1 of moderate and high dose could alleviate oxidative stress damage, improve neuroinflammation, protect neurons, finally improve the cognitive impairment of the AD tree shrew. This study provides theoretical basis for the Rg1 clinical application in AD. Abstract : Ginsenoside Rg1 could alleviate oxidative stress damage, improve neuroinflammation, regulate apoptosis, protect neurons though the Wnt/GSK‐3β/β‐catenin signaling pathway, finally improve the cognitive impairment of the AD tree shrew.